Discovery and Emancipation of Basic Science and Technology Students’ Behaviour from School Environment Constraints - Afuwape, Moses Olanrewaju; Adeyi, Funmilayo Adeola (NIU Journal of Social Sciences, 2019)
The study investigated the school environment as one of the predictors to students’ behaviour in Basic Science and Technology. The design of the study was survey type while the population comprised (50) Basic Science and Technology teachers and (450) public and private junior secondary school students in the selected local government areas in Ogbomoso Educational zone of Oyo state. A self-developed questionnaire on School environment predictors of Students behaviour in Basic Science and Technology was prepared for data collection. The instrument was validated, a cronbach Alpha reliability coefficient method was employed to ensure the reliability of the instruments. One research question and one null hypothesis guided the study. The result were analyzed using frequency count, mean and simple percentage, while t-test statistics was used to test the hypothesis at 0.05 level of significance. The result showed that unattractive school environment, non-availability of highly equipped library, non- availability of standard Basic Science and Technology laboratory, non-availability of necessary infrastructure like chairs, tables, chalkboard and shelves, Poor school principal’s inspection, Noisy environment, Indiscipline on the part of the principal, teachers and students, Insurgence and poor welfare condition. All these have significant effect on behaviour of Nigerian students towards Basic Science and Technology and also call for immediate emancipation for the sake of effective learning. Based on these findings, recommendations were made. Keywords: School environment, students’ behaviour and Basic science and Technology